KLASIFIKASI PENERIMA BANTUAN SKTM MENGGUNAKAN ALGORITMA NAIVE BAYES: STUDI KASUS DESA PESANGGRAHAN - Ahmad, Ahmad Gunawan; Zaehol Fatah, Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
Implementation of the Naive Bayes algorithm for the classification of recipients of the Certificate of Inability to Pay (SKTM) assistance in Pesanggrahan Village. The classification process is carried out manually and using the RapidMiner application to validate the results. Manual calculations are carried out by calculating the probability of each attribute, such as occupation, age, income, marital status, vehicle, and asset ownership. The calculation results show that the probability for the